PENGARUH PENGGUNAAN MEDIA KOTAK PINTAR UNTUK MENGENAL HURUF ABJAD ANAK USIA 4-5 TAHUN DI TK AS SHOFA KOTA JAMBI - Alifa Asyafila Rahmadani; Hendra Sofyan; Rizki Surya Amanda (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
The ability to recognize the letters of the alphabet is one of the fundamental aspects in the development of early childhood literacy. This research is based on the results of observations by researchers in the field who show that recognizing the alphabet letters of children aged 4-5 years at TK As Shofa, Jambi City has not developed optimally. Based on the initial findings, it is known that out of 16 children, as many as 11 children are not optimal in recognizing the letters of the alphabet. This study aims to find out the extent of the influence of the use of smart box media in improving the ability to recognize the alphabet in children aged 4-5 years. This study uses a quantitative approach with an experimental method, adopting a Pre -Experimental design with the One Group Pretest-Posttest Design model. The study population is group A children at TK As Shofa which totals 16 people, with sampling techniques using the saturated sampling method. The instrument used was in the form of an observation sheet, while the data analysis was carried out by hypothesis test using a paired samples test. The test results showed that the calculated t value of 25.564 was greater than the t of table 2.131 at the significance level of α = 0.05. This means that the use of smart box media has an effect on improving the ability to recognize the alphabet of children aged 4-5 years at TK As Shofa. Thus, smart box media can be used as an alternative in the learning process to support the introduction of alphabetic letters in early childhood Keywords:  Smart Box Media; Getting to Know the Alphabet Letters